RFID mutual authentication protocols for tags and readers with and without a server - Han, Song; Dillon, Tharam S.; Potdar, Vidyasagar; Chang, Elizabeth (C R L Publishing Ltd., 2013)
RFID has very huge potential in today's social and business developments. RFID-based identification is an example of emerging technology which requires authentication Security and Privacy are one of the important issues in the design of practical RFID protocols. In this paper, we focus on RFID authentication protocol RFID mutual authentication is used to ensure that only an authorized RFID reader can access the data of RFID tag while the RFID tag is confirmed that it releases data to the authenticated RFID reader. In this paper, we will propose two mutual authentication protocols for RFID tags: server-based authentication protocol and serverless authentication protocol. The two protocols both enable RFID reader and tag to carry out the authentication based on their synchronized secret information. In the first protocol based on a server, the synchronized secret information will be monitored by a component of the database server. In the second protocol without a server, mutual authentication does not need to rely on a back-end database. It enables RFID tags to be anonymous to RFID reader so that privacy can be preserved. © 2013 CRL Publishing Ltd.